Perilaku Cyberloafing Pegawai Pemerintahan Kecamatan di Aceh Barat - Muhammad Rahmat Hidayat; Rusdi Rusdi; Fatmayanti Fatmayanti; Angga Ardiansyah; Dede Ruhyat; Nanda Rasbima Sagala; Sayuti Sayuti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Cyberloafing is a form of social-loafing that reduces joint performance within an organization. As a reluctance to provide equal effort to communal work, cyberloafing is much more covert because an individual can hide behind their electronic work device. In the form of service work that demands teamwork, this behavior interferes with the performance of public service organizations. This study aims to see how this behavior exists in an organizational institution. This study took the research locus in sub-district offices throughout West Aceh Regency. A total of 73 research respondents consisting of government employees with the status of civil servants were examined for their responses from the main point of view of The Theory of Reasoned Action. The results of the partial least square test on the research construct indicate that the behavioral intention is based on the environment around which the individual interacts. The perceived behavioral control variable does not affect cyberloafing behavior.